2017
DOI: 10.1093/aobpla/plx020
|View full text |Cite
|
Sign up to set email alerts
|

Pollination success following loss of a frequent pollinator: the role of compensatory visitation by other effective pollinators

Abstract: Sudden declines of frequent and effective pollinators are often assumed to reduce pollination success. Yet this assumption has rarely been tested experimentally and may depend upon responses of other pollinators in the community. We temporarily excluded bumble bees in populations of the milkweed Asclepias verticillata, and quantified pollinator visitation rates and pollen receipt in both control and bumble bee exclusion plots. Asclepias pollination success did not decline following bee exclusion due to a nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…) are likely to occur, and failure of some pollinators should be followed by pollination decline less often than in depauperate habitats (Pauw , Hallett et al. ). In habitats with diverse pollinator communities, therefore, indices of pollinator abundance that are not directly linked to their pollinating activity at flowers (e.g., pan trap or Malaise trap captures; Nielsen et al.…”
Section: Pollinator Trends In Natural Habitats: a Methodological Frammentioning
confidence: 99%
See 3 more Smart Citations
“…) are likely to occur, and failure of some pollinators should be followed by pollination decline less often than in depauperate habitats (Pauw , Hallett et al. ). In habitats with diverse pollinator communities, therefore, indices of pollinator abundance that are not directly linked to their pollinating activity at flowers (e.g., pan trap or Malaise trap captures; Nielsen et al.…”
Section: Pollinator Trends In Natural Habitats: a Methodological Frammentioning
confidence: 99%
“…Wasps, for example, have been shown experimentally to replace bumble bees as efficient pollinators of Asclepias flowers (Hallett et al. ), and invasive bumble bees may replace advantageously the pollination services of declining native species (Madjidian et al. ).…”
Section: Pollinator Trends In Natural Habitats: a Methodological Frammentioning
confidence: 99%
See 2 more Smart Citations
“…Pollen limitation can have many causes (Knight et al 2005) and lower pollinator diversity in some populations of a species is certainly one of them, as Gómez et al (2010) Polistes wasps that were just as effective as pollinators (Hallett et al 2017) -an example of ecological redundancy within the system (see section 5.1). In contrast, Brosi and Briggs (2013) found that removing a single bumblebee species from localised patches reduced the reproductive success of Delphinium barbeyi (Ranunculaceae), even though alternative pollinators were present.…”
mentioning
confidence: 99%